Jesus and YHWH-texts in the synoptic gospels - Brazil, Scott (Library of New Testament studies, 2024)
Cover -- Halftitle page -- Title page -- Copyright page -- Contents -- Tables -- Abbreviations -- Preface -- Acknowledgments -- Dedication -- 1 Backgrounds and Bearings -- The Phenomenon of YHWH-Texts Applied to Jesus and Its Significance -- Interpreting New Testament Uses of the Old Testament -- Summary of the Content and Format of This Study -- 2 Matthew's Application of YHWH-Texts to Jesus -- Matthew's Christology -- Matthean Cases of Old Testament YHWH-Texts Applied to Jesus -- Conclusion -- 3 Mark's Application of YHWH-Texts to Jesus -- Mark's Christology -- Markan Cases of Old Testament YHWH-Texts Applied to Jesus -- Conclusion -- 4 Luke's Application of YHWH-Texts to Jesus -- Luke's Christology -- Lukan Cases of Old Testament YHWH-Texts Applied to Jesus -- Conclusion -- 5 Realizations and Ramifications -- Five Realizations from This Study -- Five Ramifications from This Study -- Bibliography -- Subject Index -- Scripture Index.